2020
DOI: 10.1194/jlr.ra120000664
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA Gm15622 stimulates SREBP-1c expression and hepatic lipid accumulation by sponging the miR-742-3p in mice

Abstract: Excessive lipid deposition is a hallmark of NAFLD. Although much has been learned about the enzymes and metabolites involved in NAFLD, few studies have focused on the role of long noncoding RNAs (lncRNAs) in hepatic lipid accumulation. Here, using in vitro and in vivo models of NAFLD, we found that the lncRNA Gm15622 is highly expressed in the liver of obese mice fed a HFD and in murine liver (AML-12) cells treated with free fatty acids. Investigating the molecular mechanism in the liver-enriched expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Studies indicated that miR-495 participated in the regulation of inflammatory response, which acted as a negative modulator of inflammation-motivating pathways [ 55 , 56 ]. miR-742-3p was only reported to be involved in excessive lipid deposition [ 57 ], and miR-126b was essential for lymphatic system development in mammals [ 58 ]. In addition, no article reported the relationship between miR-672-3p and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that miR-495 participated in the regulation of inflammatory response, which acted as a negative modulator of inflammation-motivating pathways [ 55 , 56 ]. miR-742-3p was only reported to be involved in excessive lipid deposition [ 57 ], and miR-126b was essential for lymphatic system development in mammals [ 58 ]. In addition, no article reported the relationship between miR-672-3p and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies focused on screening differentially expressed genes (DEGs) using RNA-seq without sufficient exploration of the function and mechanisms of the DEGs. In previous papers, a number of lncRNAs have been well characterized to be involved in adipose tissue accumulation in cells or rodents [50,64]. These studies could provide insights into the important role and application of lncRNAs in regulating the development of adipose tissue in farm animals.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 96%
“…Indeed, the lncRNA Blnc1, implicated in adipogenesis and obesity, was found upregulated in obese and NAFLD mice, activating SREBP1c and hepatic lipogenesis, thus aggravating disease progression 249 . Gm15622 was also found upregulated in the liver of obese mice fed a HFD, exerting its mechanism of action sponging miR‐742‐3p, subsequently upregulating SREBP1c 250 . Moreover, its inactivation abrogates HFD‐induced hepatic steatosis, suggesting also in this case a therapeutic window 249 .…”
Section: Lncrnas In Obesity‐associated Diseasesmentioning
confidence: 98%